2018
DOI: 10.1155/2018/1031726
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Raw Cow Milk Quality in Smallholder Dairy Farms in Pemba Island Zanzibar, Tanzania

Abstract: Milk quality depends on the physicochemical characteristics, hygienic standards, and nutritional quality; however, animal husbandry practices, unhygienic harvesting and processing, may affect its quality. A cross-sectional study was conducted between August 2010 and July 2011 to assess the hygiene of cow milk production environment, raw cow milk physicochemical characteristics, and microbial quality and estimate the prevalence of antimicrobial residues using standard methods in Pemba Island. A total of 98 raw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 22 publications
1
20
1
2
Order By: Relevance
“…Microbiological quality of raw milk: TVBC, TCC, S. aureus, yeasts and moulds and lactic acid bacteria count of raw milk was log 7.64±0.89, 6.03±1.01, 6.15±0.04, 3.23±0.02 and 6.21±0.75 cfu/ml, respectively, while the pH of raw milk was 6.7±0.3 (Table 1). TVBC and TCC in this study are lower than those of Gwandu et al 17 who reported that the mean total viable and total coliform counts were 11.02±11.6 log cfu/ml and 6.7±7.3 log cfu/ml, respectively and that up to 26.5% of milk samples had the total coliform count beyond levels. Microbiological quality of cheese: Table 2 presents the microbiological quality of cheese.…”
Section: Resultscontrasting
confidence: 82%
“…Microbiological quality of raw milk: TVBC, TCC, S. aureus, yeasts and moulds and lactic acid bacteria count of raw milk was log 7.64±0.89, 6.03±1.01, 6.15±0.04, 3.23±0.02 and 6.21±0.75 cfu/ml, respectively, while the pH of raw milk was 6.7±0.3 (Table 1). TVBC and TCC in this study are lower than those of Gwandu et al 17 who reported that the mean total viable and total coliform counts were 11.02±11.6 log cfu/ml and 6.7±7.3 log cfu/ml, respectively and that up to 26.5% of milk samples had the total coliform count beyond levels. Microbiological quality of cheese: Table 2 presents the microbiological quality of cheese.…”
Section: Resultscontrasting
confidence: 82%
“…For a clearer evaluation, all studies with salmon, other fish from aquaculture, and shrimp were combined as seafood in the evaluation, as can be seen in Figure 2 . Cattle [ 17 , 18 , 19 , 20 , 21 , 22 ], Eggs [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], Milk [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], Pork [ 58 , 59 , 60 ], Poultry [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ,…”
Section: Resultsmentioning
confidence: 99%
“…Also households that regularly consume milk in rural Uganda have recorded better health outcomes than non-milk consumers (Dobson and Combs 2005). On the other hand, the high nutritive value and water content of milk support the growth of bacterial pathogens (Ondieki et al 2017) such as Salmonella, Staphylococcus or Escherichia coli that can cause milk-borne illnesses (Gwandu et al 2018;Kateete et al 2013). These may originate from the infected cows, the milk handlers, the equipment and/or the unhygienic environment (Kateete et al 2013, Swai andSchoonman 2011;Kaneene et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Often, the prolonged use of antibiotics in udder infections exerts selection pressure which promotes resistant bacteria phenotypes (Oliver et al 2011). These are shed in milk and can lead to milk-borne infections with severe consequences among the consumers (Kuipers et al 2016;Gwandu et al 2018).…”
Section: Introductionmentioning
confidence: 99%